Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
Proceedings of the XLVIII Brasilian Congress of Engineering Education 2020
DOI: 10.37702/cobenge.2020.3232
|View full text |Cite
|
Sign up to set email alerts
|

Experiência De Ensino Remoto Emergencial Na Pós-Graduação Em Engenharia

Abstract: Resumo: A pandemia de COVID-19 trouxe desafios para o ensino nas instituições de ensino superior em todo o mundo. Neste cenário de grandes incertezas quanto à segurança sanitária de estudantes e professores, o ensino remoto emergencial tem sido uma opção adotada por diversos cursos para continuar as atividades educacionais e minimizar os impactos do distanciamento social. Assim, este artigo visa relatar a experiência de duas disciplinas de pós-graduação em engenharia civil de uma instituição pública de ensino … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 4 publications
(7 reference statements)
0
2
0
Order By: Relevance
“…In higher education, challenges, difficulties, and, at the same time, solutions for what has been called emergency remote or non-face-to-face teaching have emerged (Moreira, Henriques & Barros, 2020;Biotto & Serra, 2020). In fact, some institutions adopted the term virtualised teaching, as did a community university in South Brazil, the context of the work presented in this article, in which we analyse scenarios of undergraduate engineering courses that include basic formation subjects, such as physics, mathematics, and chemistry.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In higher education, challenges, difficulties, and, at the same time, solutions for what has been called emergency remote or non-face-to-face teaching have emerged (Moreira, Henriques & Barros, 2020;Biotto & Serra, 2020). In fact, some institutions adopted the term virtualised teaching, as did a community university in South Brazil, the context of the work presented in this article, in which we analyse scenarios of undergraduate engineering courses that include basic formation subjects, such as physics, mathematics, and chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…In the same direction, Biotto and Serra (2020) realised that remote communication and interaction tools applied in synchronous classes played an important role in connecting students and teachers. However, they found that this was insufficient to maintain motivated students who were still adapting to social distancing.…”
Section: Introductionmentioning
confidence: 99%